Synthesis of ultra-narrow PbTe nanorods with extremely strong quantum confinement - Han, Lu; Fang, Honghua; Du, Chunmiao; Sun, Jianxia; Li, Youyong; Ma, Wanli (Journal of materials science & technology, 2019)
Monodisperse, high-quality, ultra-narrow PbTe nanorods were synthesized for the first time in a one-pot, hot-injection reaction using trans-2-decenoic acid as the agents for lead precursors and tris(diethylamino)phosphine telluride together with free tris(diethylamino)phosphine as the telluride precursors. High monomer reactivity, rapid nucleation and fast growth rate derived from the new precursors led to the anisotropic growth of PbTe nanocrystals at low reaction temperatures (<150 °C). In addition, the aspect ratio of PbTe nanorods could be largely adjusted from 4 to 15 by tuning the Pb to Te precursor molar ratio and reaction temperatures. Moreover, the synthesized ultra-narrow PbTe nanorods exhibited extremely strong quantum confinement and presented unique optical properties. We revealed that the diameter and length of PbTe nanorods could significantly affect their optical properties, which potentially offer them new opportunities in the application of optoelectronic and thermoelectric devices and make them desired subjects for multiple exciton generation and other fundamental physics studies.